Didelio meistriškumo disko metiko rengimas ir parengtumas metiniame cikle: atvejo analize - Jusis, M.; Paulauskas, R. (Sporto Mokslas-Sport Science, 2024)
Analysing and describing the case of an exceptional athlete`s training in a real context and explain the peculiarities of his development activities, when the boundaries of that case and its context are not clear, becomes relevant to sports researchers and practitioners. The application of educational methods presents a new scientific problem: what physical abilities does the athlete need to achieve significant success in the discus throwing event and what training measures help to achieve this? The aim of the research: to investigate the training of a high-performance athlete - a discus thrower in the annual cycle, evaluating the effectiveness of training progress through objective readiness parameters. Research objectives: 1) To define the main parameters of a high-performance athlete the training workload volume, intensity, and distribution in the annual training cycle; 2) To evaluate the changes in the athlete`s physical abilities, readiness, and adaptation to physical loads while training in Lithuania and the United States. Regular monitoring and load tracking allowed for managing and adjusting the training program, as a decrease in performance was observed towards the end of the special training period, leading to a reduction in training load and intensity. Considering the athlete`s participation in 14 competitions over the year, the annual training cycle plan helped the athlete reach peak physical condition during the most important season competitions - the World Athletics Championships and the European Athletics Championships. Physical readiness tests showed that most indicators improved over the annual cycle leading up to the most important competitions of the season. Over the year, the athlete`s power increased faster than body mass, as demonstrated by the testing conducted with the "Vmaxpro" system and the calculated power-to-body mass ratio - from 44.35 W/kg at the beginning of the annual cycle to 51.26 W/kg at the peak of athletic form, when a personal discus throwing record of 71.43 meters was achieved during training.